2001
DOI: 10.1097/00000372-200108000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Postirradiation Pseudosclerodermatous Panniculitis

Abstract: Pseudosclerodermatous panniculitis is an unusual variant of panniculitis that results as a complication of megavoltage radiotherapy. Four women developed this unusual entity on the anterior chest and abdominal skin after receiving megavoltage therapy for either breast carcinoma or painful bone metastases from breast carcinoma. Histopathologically, the epidermis and dermis of the involved area showed little or no evidence of radiodermatitis. The main findings were confined to the subcutaneous tissue and consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 19 publications
1
24
0
2
Order By: Relevance
“…The first description by Winkelmann of 4 cases in 1993 was followed by additional 4 cases in 2001. 19,20 These cases were characterized by erythematous indurated plaques in the field of radiation. Biopsies of the affected areas revealed significant changes in the subcutaneous tissues revealing a lobular panniculitis, thickened septae, and an inflammatory infiltrate.…”
Section: Resultsmentioning
confidence: 99%
“…The first description by Winkelmann of 4 cases in 1993 was followed by additional 4 cases in 2001. 19,20 These cases were characterized by erythematous indurated plaques in the field of radiation. Biopsies of the affected areas revealed significant changes in the subcutaneous tissues revealing a lobular panniculitis, thickened septae, and an inflammatory infiltrate.…”
Section: Resultsmentioning
confidence: 99%
“…According to Winkelmann et al [6], classical radiodermatitis may also be observed. But for Carrasco et al [8], histopathological findings are essentially limited to the subcutaneous tissue. This could probably be explained by the level of the concentration of the megavoltage therapy.…”
Section: Discussionmentioning
confidence: 99%
“…All lesions begin in the irradiated area and in 25% of the reported cases, lesions spread beyond the irradiated area, and the severity is not correlated with the irradiation dose [13]. In contrast to PPAI, histopathological changes are limited to the dermis [8]. Borrelia lymphocytoma could have a similar appearance, but the blood test is usually positive and histological features are different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akut radyodermatit, radyoterapiden ortalama 3-6 gün sonra ortaya ç›kan eritemli, ödemli, vezikülobüllöz ve erode lezyonlarla karakterizedir. ‹yonize radyasyona uzun süre suberitem dozlar›nda kronik maruziyet, birkaç aydan 10-30 y›la kadar de¤iflen latent periyot içerisinde atrofi, telenjiektazi, skleroz, hipo-hiperpigmentasyon, bazal hücreli karsinom, 9 gibi dermatozlara yol açt›¤› yönünde anektodal vaka raporlar› mevcuttur. ‹rradyasyon sonras›nda ortaya ç›kan akneiform lezyonlar oldukça nadir görülmekte ve 6 aya kadar uzayabilen latent periyot sonras›nda ortaya ç›kabilmektedir.…”
Section: Giriflunclassified